Regenerative Leadership : Model Kepemimpinan yang berfokus pada Keberlanjutan dan Kesejahteraan jangka panjang Organisasi serta Lingkungan - Nur Laili Rahmawati; Achmad Faisal Al Farizy; Malika Risqi; Mochammad Isa Anshori (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Climate change, environmental degradation, and global socio-economic pressures require organizations to adopt leadership models that are more sustainable, adaptive, and future-oriented. This article aims to explore the concept of Regenerative Leadership as a leadership model that focuses on long-term sustainability and well-being for both organizations and the broader ecosystem. A Systematic Literature Review (SLR) method was employed, analyzing 20 relevant scholarly articles published between 2018 and 2023. The findings reveal that Regenerative Leadership integrates ecological values, spirituality, systemic collaboration, and holistic awareness into leadership practices. This model goes beyond organizational performance by emphasizing the restoration and regeneration of social-ecological systems. The results contribute to both theoretical development and practical application of leadership models that are responsive to complex challenges in the modern era.